2016
DOI: 10.1089/thy.2015.0470
|View full text |Cite
|
Sign up to set email alerts
|

The Natural History of Subclinical Hyperthyroidism in Graves' Disease: The Rule of Thirds

Abstract: A third each of patients with SH due to GD progress, normalize, or remain in the SH state. Older people and those with positive anti-TPO antibodies have a higher risk of progression of the disease. These novel data need to be verified and confirmed in larger cohorts and over longer periods of follow-up.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
7
1
2

Year Published

2016
2016
2020
2020

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(12 citation statements)
references
References 17 publications
2
7
1
2
Order By: Relevance
“…All these studies were of moderate size (with a mean of around 100 participants). More recent studies have focused mainly on TPOAb positivity, which was found in 76.4% of 802 French patients with GD 15; in 7% of 111 Omani GD patients [11] and in 56.8% of 44 patients with subclinical hyperthyroidism due to GD [29]. Our data of 64% TPOAb-positivity and 36% TgAb positivity show a lower prevalence than those in the listed publications.…”
Section: Discussioncontrasting
confidence: 53%
See 1 more Smart Citation
“…All these studies were of moderate size (with a mean of around 100 participants). More recent studies have focused mainly on TPOAb positivity, which was found in 76.4% of 802 French patients with GD 15; in 7% of 111 Omani GD patients [11] and in 56.8% of 44 patients with subclinical hyperthyroidism due to GD [29]. Our data of 64% TPOAb-positivity and 36% TgAb positivity show a lower prevalence than those in the listed publications.…”
Section: Discussioncontrasting
confidence: 53%
“…Our fi nding of a positive association of TPOAb levels with serum fT4 is intriguing, but it could be also due to a lower type II deiodinase enzyme activity [36]. In a study addressing the natural history of subclinical hyperthyroidism in GD, positive TPOAb were associated with risk of progression to overt hyperthyroidism -with hazard ratios from 1.06 to 10.15 per year [29]. In a histological study higher TPOAb levels were correlated with intra-thyroidal germinative center development, suggesting a more aggressive immunological attack [37].…”
Section: Discussionmentioning
confidence: 83%
“…Thyroid diseases, specifically subclinical conditions, can revert to euthyroid status over time (Somwaru et al. 2012; Zhyzhneuskaya et al. 2016).…”
Section: Methodsmentioning
confidence: 99%
“…In addition, in the presence of TSH-R-Ab indicating "subclinical" GD, the rate of progression to overt hyperthyroidism is up to 30% in the subsequent 3 years [83]. Therefore, despite the absence of randomized trials, treatment is indicated in patients older than 65 years with a TSH that is persistently < 0.1 mIU/L to potentially avoid these serious adverse events and the risk of progression to overt hyperthyroidism.…”
Section: ∅∅∅○mentioning
confidence: 99%